Sette adolescenti in cerca di autore - Fagioli, Francesca (Il sogno della farfalla, 2018)
This short article proposes a reflection on the work being carried out within a therapeutic community for adolescents, identifying its shortcomings and challenges not only in its being understaffed but also in the fragility and the problems of these peculiar psychiatric patients. For instance, adolescents experience both physiological growth entailing crises and changes and deep malaise that often emerges through behaviour disturbances and self-harming actions. The therapeutic work must therefore involve both adolescents and their families and have the specific education of the personnel as a prerequisite.